Induction of the germ cell fate from pluripotent stem cells in cynomolgus monkeys. Issue 3 (13th November 2019) - Sakai, Yoshitake; Nakamura, Tomonori; Okamoto, Ikuhiro; Gyobu-Motani, Sayuri; Ohta, Hiroshi; Yabuta, Yukihiro; Tsukiyama, Tomoyuki; Iwatani, Chiduru; Tsuchiya, Hideaki; Ema, Masatsugu; Morizane, Asuka; Takahashi, Jun; et al.
Abstract: In vitro reconstitution of germ-cell development from pluripotent stem cells (PSCs) has created key opportunities to explore the fundamental mechanisms underlying germ-cell development, particularly in mice and humans. Importantly, such investigations have clarified critical species differences in the mechanisms regulating mouse and human germ-cell development, highlighting the necessity of establishing an in vitro germ-cell development system in other mammals, such as non-human primates. Here, we show that multiple lines of embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) in cynomolgus monkeys ( Macaca fascicularis ; cy) can be maintained stably in an undifferentiated state under a defined condition with an inhibitor for WNT signaling, and such PSCs are induced efficiently into primordial germ cell-like cells (PGCLCs) bearing a transcriptome similar to early cyPGCs. Interestingly, the induction kinetics of cyPGCLCs from cyPSCs is faster than that of human (h) PGCLCs from hPSCs, and while the transcriptome dynamics during cyPGCLC induction is relatively similar to that during hPGCLC induction, it is substantially divergent from that during mouse (m) PGCLC induction. Our findings delineate common as well as species-specific traits for PGC specification, creating a foundation for parallel investigations into the mechanism for germ-cell development in mice, monkeys, and humans. Abstract : Pluripotent stem cells in cynomolgus monkeys are induced into primordial germ cell-like cells with species-specific kinetics and transcriptome dynamics.